Assessing entomological risk factors for arboviral disease transmission in the French Territory of the Wallis and Futuna Islands. - Elodie Calvez; Nicolas Pocquet; Atoloto Malau; Sosiasi Kilama; Alefosio Taugamoa; Didier Labrousse; Philippe Boussès; Anna-Bella Failloux; Myrielle Dupont-Rouzeyrol; Françoise Mathieu-Daudé (Public Library of Science (PLoS), 2020)
BACKGROUND:The French overseas Territory of the Wallis and Futuna Islands has been affected by several dengue epidemics. Aedes polynesiensis is the main mosquito vector described in this territory. Other Aedes species have been reported, but recent entomological data are missing to infer the presence of other potential arbovirus vectors and to assess the entomological risk factors for transmission of arboviral diseases. METHODOLOGY/ PRINCIPAL FINDINGS:An entomological prospective study was conducted on the three main islands of the territory to determine the presence and distribution of Aedes spp. Larvae, pupae and adult mosquitoes were collected from 54 sampling points in different environments, with a final sampling of 3747 immature stages and 606 adults. The main identified breeding sites were described. Ae. polynesiensis was found in every sampled site in peridomestic and wild habitats. Ae. aegypti was only found on the island of Wallis in peridomestic environments with a limited distribution. Two other Aedes species endemic to the Pacific were recorded, Aedes oceanicus and Aedes futunae. To evaluate the ability of local Ae. polynesiensis to transmit the chikungunya virus (CHIKV), two field populations were analyzed for vector competence using experimental oral exposure of females to CHIKV and infection, dissemination and transmission assays. Results showed that both populations of Ae. polynesiensis were competent for CHIKV (30% at 7 days post-infection). CONCLUSIONS/SIGNIFICANCE:This study showed the ubiquitous distribution and abundance of Ae. polynesiensis on the three islands and demonstrated that local populations were able to transmit CHIKV. Combined with the presence and expansion of Ae. aegypti on the main island of Wallis, these data highlight the risk of transmission of arboviral diseases in the territory of Wallis and Futuna and provide relevant information for entomological surveillance and vector control programs.